Pengaruh Penerapan Metode Ceramah terhadap Pemahaman Siswa pada Pelajaran Sosiologi Kelas XII IPS 5 di SMAN 1 Pasaman - Rihadhatul Aisya; Yanti Sri Wahyuni; Hefni Hefni (Journal on Education, 2023)
This research was motivated by teachers at SMAN 1 Pasaman who taught in class XII social studies 5 using the lecture method in the learning process. Judging from the level of students' understanding of the material provided by teachers in Sociology subjects is still relatively low. This study aims to find out 1) an overview of the lecture method, 2) an overview of the level of understanding of students and 3) the influence of the application of the lecture method on the level of understanding of students. The theory used in this study is cognitivism, which emphasizes that a person's behavior is determined by the perception of his understanding of situations related to the purpose of learning. Types of descriptive quantitative research corelation. The population in the study were 34 students of class XII IPS 5 at SMAN 1 Pasaman. Sampling using total sampling technique. The instrument used for research was a closed questionnaire using the Pearson correlation test. The results showed that: (1) the lecture method was in the "Very High" category with a percentage of 67.6%, (2) the level of understanding was in the "Very High" category with a percentage of 70.6%, and (3) there was the relationship between the two variables is positive and significant between the lecture method (X) and the level of understanding (Y) of students with r count > r table, namely 0.906 > 0.338 and t count > t table, namely 2.036. The conclusion is that there is an influence between the two variables which is positive and significant between the lecture method and the level of understanding of students and it is suggested for academics to make the results of this study as teaching materials for sociology education students in applying the lecture method as a teaching method in sociology lessons.